PENGARUH KEPUASAN KERJA DAN SEMANGAT KERJA TERHADAP KOMITMEN ORGANISASI DAN ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) PADA KARYAWAN HOTEL COMFORT DUMAI - Wibisono, Albertus Agung; J M Marpaung, Rio; ', Nuryanti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This study aims to analyze the influence of Job Satisfaction and Morale on Organizational Commitment and Organizational Citizenship Behavior (OCB) on the of employees Hotel Comfort Dumai. The sampling method using a census of all the population being sampled. The data used in this study is primary data obtained from questionnaires. The total sample of 108 respondents who are employees of Hotel Comfort Dumai. The analysis technique used is path analysis method. The results showed that variable Job Satisfaction, Morale, and Organizational Commitment positive and significant effect on Organizational Citizenship Behavior. The variable that has the most dominant influence on Organizational Citizenship Behavior is a Morale variable. Of this study obtained Rsquare value of 0,879, this means that 87.9% Organizational Citizenship Behavior variable can be explained by variable Job Satisfaction, Morale and Organizational Commitment and the remaining 12.1% is explained by other variables outside the equation.Keywords: Job Satisfaction, Morale, Organizational Commitment, Organizational Citizenship Behavior.